Analysis Of The Normandy Landings Operation In The Second World War From The Perspective Of Comparative Military Resources Between The Allied And Germany - Tsaniyah Wulandari; Novky Asmoro (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
World War II was a global conflict involving multiple nations, with significant impacts on the world. One notable event in the history of this war was the Normandy Landings, which served as a turning point in the Allied effort to liberate Europe from German control. This paper aims to analyze the background and comparative perspective of the military resources between the Allied forces and Germany in the Normandy Landings operation, using a qualitative method that relies on literature studies as a source to gain an accurate understanding of the events. World War II occurred as a result of the ambitions of the defeated countries in World War I. The Normandy Landings operation was a defensive assault by the Allies to maintain their presence in the Western region and prevent it from falling under the Axis allianc. The Normandy landing operation carried out by the Allies with good preparation, strategy, and superiority in defense equipment resources became a factor in the victory for the Allies.